How Valuable is Experience? Examining the Impact of Founder Experience on Nonprofit Start-Up Success (Journal of Public and Nonprofit Affairs, 2020)
Nonprofit entrepreneurs face a number of liabilities that are particularly significant during the emergent phase of a new nonprofit. Using a human capital perspective, this study examines the influence previous experience plays as it relates to nonprofit organizational start-up success. The study draws on a sample of 118 nascent nonprofit entrepreneurs. The results from a logistic regression analysis show no significant impact with regard to education or prior nonprofit management experience. The results, however, show that prior start-up experience significantly enhances the likelihood of start-up success.